The Constituent Year Effect: Relative Age Disparities in Australian Masters Track and Field Athletic Participation - Nikola Medic; Jasmine Lares; Bradley W. Young (MDPI AG, 2018)
The constituent year effect, a source of relative age disparities, in masters sport has been demonstrated mainly amongst North American samples. Thus, the purpose of this study was to examine whether a participation-related constituent year effect exists among athletes (n = 6492) competing in Australian Masters Athletics competitions between 2000 and 2014. The results indicated that a participation-related constituent year effect was observed as the likelihood of participating was significantly higher for masters athletes in their first and second constituent year of any five-year age category (p < 0.0001) and was lower when they were in the fourth or fifth constituent year. The results also indicated this effect is influenced by gender and age. Specifically, the effect was significant for both male (p < 0.0001) and female (p < 0.001) masters athletes; as well during the third, sixth, seventh, and eighth + decades of life (all ps < 0.001). These data demonstrate that despite masters sport being an avenue for promotion of participation and overall health, there is potential for improving how competitive organizational strategies are implemented given the recurring intermittent patterns of participation associated with five-year age brackets which are likely to compromise benefits.